Startups in economics: definition, essence and characteristics - Sataev Pavel (Peter the Great St. Petersburg Polytechnic University, 2021)
The relevance of the issue of researching startups is due to the emphasis on new technologies in the modern economy and the fact that startups create innovations. New opportunities are opening up for organizations that innovate. The concept of a startup is used both as a designation for an organization with specific characteristics and as a stage in the life cycle of an organization. The content of the term is ambiguous, the characteristics of startups can include such elements as innovation (creation of innovative products or services, or work on an innovative business model), potential (there is a hypothesis that startups will go through the stage of scaling after entering the market and will be able to occupy a significant market share), short term of work, high risk, small size, temporary condition. Different studies emphasize different characteristics. A clear designation of the term is necessary for unambiguous understanding in the context of scientific and other works without the need for additional clarifications. In addition, defining the term startup and its key elements is necessary, for example, to conduct research or to support organizations that create innovations. The review article examines existing approaches to startups, examines their key features, which are noted in various sources. The author's definition of the term is given. In addition, the article examines the life cycle of a startup in order to consider the approach to a startup as a stage of the life cycle and clarify the content of the term. Reports and databases in which the concept of "start-up" is used, provisions on start-up visas in different countries, domestic practice of working with the term "Start" (support program and the Draft Regulations on the support of start-up studios), as well as approaches of S. Blank and E. Ries and the scientific community are investigated in the work as sources. The characteristics of a startup from different sources are revealed. The frequency of use of the characteristic is indicated. The conclusion about the interpretation of the term is made.